The Effect of Cold Water Intake on Nausea and Vomiting in Cancer Patients Undergoing Chemotherapy - Ayu Safitri, Devita; Maryuni, Sri; Erwin, Tubagus (Java Nursing Journal, 2025)
Background: Cancer is a significant global health issue, with incidence rates continuing to rise and affecting millions of people. Purpose: This study aims to evaluate the effect of cold water consumption on nausea and vomiting in cancer patients undergoing chemotherapy at RSUDAM, Lampung in 2024. Methods: A quantitative approach was used with a pre-experimental design involving two groups: an intervention group that received cold water and a control group that received anti-nausea medication. Data were collected from 38 respondents, 19 in each group, using a Numeric Rating Scale (NRS) to assess the severity of nausea before and after the intervention. Findings: A quantitative approach was used with a pre-experimental design involving two groups: an intervention group that received cold water and a control group that received anti-nausea medication. Data were collected from 38 respondents, 19 in each group, using a Numeric Rating Scale (NRS) to assess the severity of nausea before and after the intervention. Conclusion: This study supports the use of cold water therapy as an adjunct treatment for managing nausea in cancer patients undergoing chemotherapy, thereby improving the overall quality of care.